Clutter in Electronic Medical Records: Examining Its Performance and Attentional Costs Using Eye Tracking. (June 2015) - Moacdieh, Nadine; Sarter, Nadine
Objective: The objective was to use eye tracking to trace the underlying changes in attention allocation associated with the performance effects of clutter, stress, and task difficulty in visual search and noticing tasks. Background: Clutter can degrade performance in complex domains, yet more needs to be known about the associated changes in attention allocation, particularly in the presence of stress and for different tasks. Frequently used and relatively simple eye tracking metrics do not effectively capture the various effects of clutter, which is critical for comprehensively analyzing clutter and developing targeted, real-time countermeasures. Method: Electronic medical records (EMRs) were chosen as the application domain for this research. Clutter, stress, and task difficulty were manipulated, and physicians' performance on search and noticing tasks was recorded. Several eye tracking metrics were used to trace attention allocation throughout those tasks, and subjective data were gathered via a debriefing questionnaire. Results: Clutter degraded performance in terms of response time and noticing accuracy. These decrements were largely accentuated by high stress and task difficulty. Eye tracking revealed the underlying attentional mechanisms, and several display-independent metrics were shown to be significant indicators of the effects of clutter. Conclusion: Eye tracking provides a promising means to understand in detail (offline) and prevent (in real time) major performance breakdowns due to clutter. Application: Display designers need to be aware of the risks of clutter in EMRs and other complex displays and can use the identified eye tracking metrics to evaluate and/or adjust their display.